Men of bronze : hoplite warfare in ancient Greece - Kagan, Donald; Kagan, Donald; Viggiano, Gregory; Viggiano, Gregory (Princeton University Press, 2017)
The papers published in this volume resulted from a conference on early Greek hoplite warfare held at Yale University in April 2008. The idea for the conference grew out of a spirited debate that took place following a panel presentation at the American Philological Association's annual meeting at San Diego in January 2007, 'New Perspectives on Ancient Warfare'